2022
DOI: 10.1021/acs.inorgchem.1c03897
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Ir(III) Phosphors to Strategically Manage Charge Recombination for High-Performance White Organic Light-Emitting Diodes

Abstract: Constructing high-quality white organic light-emitting diodes (WOLEDs) remains a big challenge because of high demands on the electroluminescence (EL) performance including high efficiency, excellent spectral stability, and low roll-off simultaneously. To achieve effective energy transfer and trap-assisted recombination in the emissive layer, herein, four Ir­(III) phosphors, namely, m OMe-Ir-PI (1), p OMe-Ir-PI (2), m OMe-Ir-PB (3), and p OMe-Ir-PB (4), were strategically designed via simple regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…For example, in the case of SFIriqa, its structure can be inferred by the bite angles of O1-Ir1-N4 [76.1(2)], N1-Ir1-C1 [80.1(2)], and N5-Ir1-C8 [80.3(2)], and twisted angles of O1-Ir1-C1 [173.9(2)], N1-Ir1-N5 [171.1(2)], and N4-Ir1-C8 [170.7(2)]. The iridium(III) atom is coordinated by two cyclometalated ligands and one auxiliary ligand with similar configuration to that of previously reported Ir(III) complexes [41][42][43][44]. The distances for SFIriqa between the Ir center and the ancillary ligand (Ir1-O1 = 2.152(5) Å and Ir1-N4 = 2.156(5) Å) are longer than those between the Ir center and the main ligand (Ir1-N1 = 2.043(5) Å and Ir1-N5 = 2.059(5) Å).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…For example, in the case of SFIriqa, its structure can be inferred by the bite angles of O1-Ir1-N4 [76.1(2)], N1-Ir1-C1 [80.1(2)], and N5-Ir1-C8 [80.3(2)], and twisted angles of O1-Ir1-C1 [173.9(2)], N1-Ir1-N5 [171.1(2)], and N4-Ir1-C8 [170.7(2)]. The iridium(III) atom is coordinated by two cyclometalated ligands and one auxiliary ligand with similar configuration to that of previously reported Ir(III) complexes [41][42][43][44]. The distances for SFIriqa between the Ir center and the ancillary ligand (Ir1-O1 = 2.152(5) Å and Ir1-N4 = 2.156(5) Å) are longer than those between the Ir center and the main ligand (Ir1-N1 = 2.043(5) Å and Ir1-N5 = 2.059(5) Å).…”
supporting
confidence: 63%
“…The iridium(III) atom is coordinated by two cyclometalated ligands and one auxiliary ligand with similar configuration to that of previously reported Ir(III) complexes. [41][42][43][44] The distances for SFIriqa between the Ir center and the ancillary ligand (Ir1-O1 = 2.152(5) Å and Ir1-N4 = 2.156(5) Å) are longer than those between the Ir center and the main ligand (Ir1-N1 = 2.043(5) Å and Ir1-N5 = 2.059(5) Å). Therefore, it can be concluded that the complexes have been successfully prepared according to all of the characterization results.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…However, while weak electron-donors cause just a little effect on absorption of the complexes, 33 strong π-donors in the ligands induce a red-shift of the absorption maxima tailing to 600 nm but do not lead to a significant enhancement of extinction coefficients for these bands. 34–37 In fact, such modifications of the ligands result in a dramatic drop of the metal d-orbitals contribution to the highest occupied molecular orbital (HOMO) of the complexes decreasing the intensity of the metal-to-ligand charge transfer (MLCT) bands. 24…”
Section: Introductionmentioning
confidence: 99%
“…Cyclometalated iridium(III) complexes have proved to be the best emitters in phosphorescent organic light-emitting diodes (PHOLED) due to their bright luminescence, appropriate excited state lifetimes, high thermodynamic and kinetic stability, and fine tuneability of the emission color by simple ligand variation [ 1 , 2 ]. These complexes are also considered as effective photocatalysts [ 3 , 4 ] and promising photosensitizers in solar cells [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%